2016
DOI: 10.1038/srep21108
|View full text |Cite
|
Sign up to set email alerts
|

Experimental warming of a mountain tundra increases soil CO2 effluxes and enhances CH4 and N2O uptake at Changbai Mountain, China

Abstract: Climatic warming is expected to particularly alter greenhouse gas (GHG) emissions from soils in cold ecosystems such as tundra. We used 1 m2 open-top chambers (OTCs) during three growing seasons to examine how warming (+0.8–1.2 °C) affects the fluxes of carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) from alpine tundra soils. Results showed that OTC warming increased soil CO2 efflux by 141% in the first growing season and by 45% in the second and third growing season. The mean CH4 flux of the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 60 publications
(87 reference statements)
3
22
3
Order By: Relevance
“…This disproves our second hypothesis that warming stimulated N 2 O emission under the treatments of vascular plant removal and can be attributed to soil moisture reduction. As a result of soil moisture reduction, N 2 O easily enters into the anaerobic zone and is consumed by denitrification [31]. However, we did not find a significant relationship between soil moisture and N 2 O fluxes under the combination of warming and vascular plant removal (W-Sh-Se).…”
Section: The Effects Of Treatments On N 2 O Fluxescontrasting
confidence: 75%
“…This disproves our second hypothesis that warming stimulated N 2 O emission under the treatments of vascular plant removal and can be attributed to soil moisture reduction. As a result of soil moisture reduction, N 2 O easily enters into the anaerobic zone and is consumed by denitrification [31]. However, we did not find a significant relationship between soil moisture and N 2 O fluxes under the combination of warming and vascular plant removal (W-Sh-Se).…”
Section: The Effects Of Treatments On N 2 O Fluxescontrasting
confidence: 75%
“…soil NH4 + -N and soil moisture (Fig. 5), unsupported our hypothesis, but it is consistent with most research results (Wu et al, 2016;Zhou et al, 2016b;Chen et al, 2017a). In addition, large inter-annual variation was observed (CV = 41.4%) during our experiment (Table 1), while the variation of annual precipitation and air temperature were only 4.41% and 7.78%, respectively (Table 1), but close to the CV of spring root biomass of ephemeral plants (47.14%) with 24 times of aboveground biomass of spring ephemeral plants in 2016 than that in 2015 (Cui et al, 2017), which indicated that the increase of Rs in 2016 was mainly from the root respiration of ephemeral plants.…”
Section: Temporal Variation In Treatments On Rs and Controlling Factorssupporting
confidence: 93%
“…14:00 by warming, which may reduce carbon emission from soil to atmosphere. However, this is not consistent with results from a tundra ecosystem, subtropical forest or alpine regions where Rs was significantly increased by warming due to the limitation of soil temperature in these ecosystems, and no significant change in soil moisture (Noh et al, 2016;Wu et al, 2016;Zhou et al, 2016b). In addition, a significant increase in Rs was found following enhanced precipitation with warming ( Fig.…”
Section: Single-factors Impacts Of Precipitation N Deposition and Wacontrasting
confidence: 73%
“…Gas samples were drawn through a three-way stopcock, using a 60 ml syringe, and then transferred for storage into 500 ml aluminium foil gas-collecting bags (China Dalian Delin Gas Packing Co., Ltd). Four gas samples of approximately 250 ml were taken in each chamber at four time intervals for each sampling event (0, 10, 20 and 30 min) from 9:00 am at local time to represent daily mean flux51. Temperatures inside the chamber and at soil or manure depths of 50 mm were also recorded on each sampling occasion.…”
Section: Methodsmentioning
confidence: 99%